Capturing the teaching of English oral skills in an Indonesian university: classroom activities and pedagogical challenges - Evi Puspitasari; Melliana Fitria Eka Dewi (Journal on English as a Foreign Language, 2023)
In the context of English as a foreign language, listening and speaking skills are frequently discussed in isolation. In fact, to improve students' language mastery, the skills had better be taught in an integrated way. This research aimed to unveil activities for teaching oral skills that teachers implemented and discussed their challenges in the implementation. The data of this case study were obtained by observing three classes and interviewing three university teachers who taught integrated listening and speaking skills in an English language education department of a university in Indonesia. To analyze data gained from the interview, we used open, analytical, axial, and selective coding to identify the emerged themes using thematic analysis. Findings revealed that discussion, information gap, role play and simulation, and oral presentation were applied in the classrooms. The study also revealed that the challenges of applying the activities come not only from the students' side, such as their anxieties, low participation, and tendency to use their first language, but also from the teachers' part regarding their classroom management skills. Those findings implied that the success of oral skill instruction is achievable through various activities that involve students' listening and speaking skills at once.